2021
DOI: 10.3390/antiox10040540
|View full text |Cite
|
Sign up to set email alerts
|

Total Analysis of the Major Secoiridoids in Extra Virgin Olive Oil: Validation of an UHPLC-ESI-MS/MS Method

Abstract: Extra virgin olive oil (EVOO), one of the key foods of the Mediterranean diet, is distinguished by its high content of nutritional and antioxidant compounds compared to other vegetable oils. During EVOO production, the major secoiridoids of EVOO, oleacein, oleocanthal, ligstroside, and oleuropein aglycones, undergo a series of transformations to open- and closed-structure forms. The resulting mixture of compounds can become more complex during the analytical procedure, due to the keto-enol tautomerism of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The identification and quantification of individual phenolic compounds were carried out by liquid chromatography coupled to mass spectrometry in tandem mode (LC-MS/MS) following the methodology described in López-Yerena et al [ 18 ] and Lozano-Castellón et al [ 19 ] with few modifications. An Acquity TM UPLC (Waters; Milford, MA, USA) coupled to an API 3000 triple-quadrupole mass spectrometer (PE Sciex, Concord, ON, Canada) with a turbo ion spray source was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification and quantification of individual phenolic compounds were carried out by liquid chromatography coupled to mass spectrometry in tandem mode (LC-MS/MS) following the methodology described in López-Yerena et al [ 18 ] and Lozano-Castellón et al [ 19 ] with few modifications. An Acquity TM UPLC (Waters; Milford, MA, USA) coupled to an API 3000 triple-quadrupole mass spectrometer (PE Sciex, Concord, ON, Canada) with a turbo ion spray source was used.…”
Section: Methodsmentioning
confidence: 99%
“…The column and precolumn were an Acquity UPLC ® BEH C18 column (2.1 × 50 mm, i.d., 1.7 µm particle size) and Acquity UPLC ® BEH C18 Pre-Column (2.1 × 5 mm, i.d., 1.7 µm particle size) (Waters Corporation ® , Wexford, Ireland), respectively. Two methods were used: method (a) for the identification of oleacein, oleocanthal, and ligstroside and oleuropein aglycone [ 19 ], and (b) for the identification of other phenolic compounds [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Before the distribution experiment, the ROO (vehicle) was analyzed by LC-ESI-LTQ-Orbitrap-MS to make sure it was free of phenolic compounds. The liquid–liquid extraction of phenolic compounds of ROO was performed following the previously described procedures [ 33 ]. The chromatographic and mass spectrometer conditions were the same as those used for the identification of metabolites ( Section 2.3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Oleuropein has several pharmacological properties with scientific proof, among which we can mention: antioxidant, antimicrobial and antiviral activities, in addition to anti-atherogenic and anti-inflammatory potential. The vasodilation, antiplatelet, hypotensive, antirheumatic, diuretic, antipyretic (Mao et al, 2019) and protective effects on male reproductive (Lozano-Castellón et al, 2021;Rostamzadeh et al, 2020) are related to oleuropein Ethnopharmacological studies demonstrated that oleuropein have therapeutic potential for gastric ulcers (Koc et al, 2020).…”
Section: Others Pharmacological Effects Of Oleuropeinmentioning
confidence: 99%